Analysis of Determining the Types of Wireless BTS Devices Using the Dude Implementation and Telegram Notifications on Internet Services Provider XYZ - Robertus Saptoto; Bambang Purnomosidi DP; Widyastuti Andriyani; Rikie Kartadie (LPPM UTDI (d.h STMIK AKAKOM) Yogyakarta, 2022)
ISP XYZ is a company engaged in the field of Internet Service Providers (ISP). Network monitoring is something that an ISP must have in monitoring network router traffic, wireless Base Transceiver Station (BTS) traffic and wireless client traffic. Connections between BTS backbone and BTS use wireless devices. Because currently the main network (backbone) inter BTS to BTS uses wireless devices, sometimes disturbances occur such as frequency interference and high data loads on BTS which lead data distribution to customers disrupted. The factors that affect this incident are the number of similar frequency number usage, the distance between BTS to BTS, the type of wireless device that can no longer carry large data loads as its main source. Telegram makes it possible to send and receive text messages over the internet. In addition, the function of telegram is usable. This research will be used to determine policies for updating wireless devices, especially on the BTS to BTS backbone. Chat, video calls, shared photos and files, telegram supports bots. This bot will later be used to mechanize notifications from the dude application to telegram messages, which of course are connected to the internet. You can provide reports on the use of data traffic, wireless device data resources that are currently implemented.